VD_FINDINFO Jug / 2024 / 159 vom 5. Dezember 2023 - VD Tribunal cantonal (2023)
ESCROQUERIE, PAR MÉTIER, BLANCHIMENT D'ARGENT, CRÉANCE, PRÉTENTION DE DROIT PUBLIC | 146 al. 1 CP, 146 al. 2 CP, 251 CP, 305bis CP, 71 al. 1 CP